2002
DOI: 10.1002/ajmg.10511
|View full text |Cite
|
Sign up to set email alerts
|

Maternal isodisomy for 14q21‐q24 in a man with diabetes mellitus

Abstract: We report a 20-year-old man with maternal uniparental disomy for chromosome 14 (UPD14) and maturity-onset diabetes mellitus (DM). He had pre- and postnatal growth retardation, developed DM at age 20 years without any autoimmune antibodies, and had a mosaic 45,XY,der(14;14)(q10;q10)[129]/46,XY,+14,der(14;14)(q10;q10)[1] karyotype. Allelotyping using microsatellite markers covering the entire 14q indicated segmental maternal isodisomy for 14q21-q24 and maternal heterodisomy of the remaining regions of the chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Of 15 patients over the age of 11 years, 3 developed diabetes mellitus; at the ages of 12 years,6 19 years25 and 20 years 31. All three patients were described as having features of type 2 diabetes, and one case was confirmed as negative for antipancreatic antibodies.…”
Section: Metabolicmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 15 patients over the age of 11 years, 3 developed diabetes mellitus; at the ages of 12 years,6 19 years25 and 20 years 31. All three patients were described as having features of type 2 diabetes, and one case was confirmed as negative for antipancreatic antibodies.…”
Section: Metabolicmentioning
confidence: 99%
“…All three patients were described as having features of type 2 diabetes, and one case was confirmed as negative for antipancreatic antibodies. Where treatment was described, oral hypoglycaemics were effective 31. BMI was significantly raised in two of the three patients (BMI 40.86 and 30.825); however, the third had a normal BMI of 24.1 31…”
Section: Metabolicmentioning
confidence: 99%
“…Two cases were ascertained by autosomal recessice disorders, alpha1 antitrypsin deficiency in one [Blayau et al, 2002] and rod monochromacy in the other [Pentao et al, 1992]. Psychomotor development and intelligence are variable and range from normal [Temple et al, 1991;Pentao et al, 1992;Coviello et al, 1996;Link et al, 1996;Desilets et al, 1997;Splitt and Goodship, 1997;Fokstuen et al, 1999;Hordijk et al, 1999;Worley et al, 2001;Giunti et al, 2002] or almost normal Tomkins et al, 1996;Sanlaville et al, 2000] to moderate mental retardation Barton et al, 1996;Kayashima et al, 2002;Cox et al, 2004]. UPD 14 is specific as many cases are associated with a Robertsonian translocation.…”
Section: Maternal Upd 14mentioning
confidence: 99%
“…Other anomalies such as a bifid uvula [Temple et al, 1991], a cleft palate [Barton et al, 1996], a persistent ductus arteriosus [Miyoshi et al, 1998], or hypogonadism [Link et al, 1996] were rarely reported. MODY (maturity-onset diabetes of the young) has been described in two cases [Manzoni et al, 2000;Kayashima et al, 2002]. Two cases were ascertained by autosomal recessice disorders, alpha1 antitrypsin deficiency in one [Blayau et al, 2002] and rod monochromacy in the other [Pentao et al, 1992].…”
Section: Maternal Upd 14mentioning
confidence: 99%
“…The exact prevalence of these conditions is unknown, and there are less than 100 cases of TS14, and fewer than 50 cases of mosaic trisomy 14 described in the literature [Ioannides et al, 2014;Salas-Labadia et al, 2014;Kagami et al, 2017]. A mole cularly and cytogenetically confirmed combination of UPD(14)mat and mosaic trisomy 14 have been currently reported only in 8 live-born cases [Antonarakis et al, 1993;Kayashima et al, 2002;Cox et al, 2004;Pecile et al, 2015;Stalman et al, 2015;Balbeur et al, 2016;Zhang et al, 2016;Ushijima et al, 2017].…”
mentioning
confidence: 99%